Pushing through: Mental health consumers' experiences of an individual placement and support employment programme. (November 2016) - Coombes, Kate; Haracz, Kirsti; Robson, Emma; James, Carole
Introduction: Individual placement and support is recognized as current best practice vocational rehabilitation for people living with a severe mental illness. This study aimed to provide insight into the consumer perspective of factors that impact the success of an individual placement and support programme in Australia. Method: A qualitative study was conducted using semi-structured interviews with five participants. Participants were diagnosed with a severe mental illness and were engaged with an individual placement supported employment programme in one area health service in New South Wales, Australia. Data analysis was conducted using grounded theory methods. Results: Analysis revealed the core category of pushing through, a three-step process that involved experiencing discomfort, learning to adapt, and getting into a groove. Pushing through described the participants' direct experience of individual placement and support, as well as their management of their health and ability to cope with everyday practicalities and relationships while engaged in the programme. Conclusions: The participants in this study described their experiences of being involved in an individual placement and support programme as being characterized by a process of pushing through. The participants' actions and experiences at each stage of this process provide cues for more tailored support within individual placement and support to meet changing needs.